Biological treatment in resistant adult-onset Still’s disease: A single-center, retrospective cohort study - Seda Çolak,; Emre Tekgöz,; Maghrur Mammadov,; Muhammet Çınar,; Sedat Yılmaz, (Archives of Rheumatology, 2022)
Objectives: The aim of this study was to assess the demographic and clinical characteristics of patients with adult-onset Still’s disease (AOSD) under biological treatment. Patients and methods: This retrospective cohort study included a total of 19 AOSD patients (13 males, 6 females; median age: 37 years; range, 28 to 52 years) who received biological drugs due to refractory disease between January 2008 and January 2020. The data of the patients were obtained from the patient files. The response to the treatment was evaluated based on clinical and laboratory assessments at third and sixth follow-up visits. Results: Interleukin (IL)-1 inhibitor was prescribed for 13 (68.4%) patients and IL-6 inhibitor prescribed for six (31.6%) patients. Seventeen (89.5%) patients experienced clinical remission. Conclusion: Biological drugs seem to be effective for AOSD patients who are resistant to conventional therapies. Due to the administration methods and the high costs of these drugs, however, tapering the treatment should be considered, after remission is achieved.